Islam, Korupsi dan Struktur Politik di Indonesia - Herlina, Lina; Nurdin, Ahmad Ali (Jurnal Review Politik, 2017)
This article departs from the author's interest in answering the question 'why most corruptors are Muslims?' Then, the author decides to make Islam, corruption and the political-bureaucratic structure in Indonesia as the theme of the discussion. There are two things that cause the emergence or the growth of corruption in Indonesia namely; first, the bureaucratic-political structure and the second: the understanding of the values of goodness (Islamic value). The political and bureaucratic structures have the most significant influence not only in Indonesia but also globally (Yaw M. Mensah: 2012). Beside, a lack of understanding about Islamic rules also causes why some Muslims like politicians, are trapped in corruption cases. Therefore, there are two solutions that can be put forward namely; firstly, the restoration of political structure and bureaucracy, and secondly, anticipate with the understanding of Islam wholly and integrity (kaffah)